Research on bidding mechanism and strategy of hydropower unit based on coupling resources. Issue 1 (February 2021) - Ding, Wenjiao; Lu, Zhanhui; Wang, Bangcan; He, Peishan; Liu, Yu; Liu, Runze; Jing, Zhaoxia
Abstract: The construction of the electric power spot market in China is at an initial stage, and there is a contradiction between the bidding mode of single-unit bidding and the physical operating characteristics of cascade generating units. When all generators in the market make price declarations and settlements independently, the dispatching and clearing results may violate the operating performance of the actual units, bring difficulties to the unit joint bidding, and at the same time cause serious deviations in scheduling and waste of actual resources. Therefore, for the power generation resources coupled with resources such as cascade hydropower units, this paper proposes a bidding mechanism based on aggregation nodes. First, the bidding mechanism and bidding strategy of the aggregation node is introduced in detail, and then the spot market-clearing model of the aggregation node bidding is established. Finally, the IEEE5 simulation shows that the bidding mechanism based on the aggregation node can make the market-clearing result reflect the unit's willingness to trade, effectively allocate cascade hydropower generation resources, and improve market transaction efficiency.